Types, Mechanisms, and Efficiency Rate of Galvanized Steel as Corrosion Protection in Atmospheric Corrosion: A Systematic Review - Trihol Oky Jones Silaban; Angga Fajar Setiawan; Suprapto Siswosukarto; Ardi Wiranata; Ryan Anugrah Putra; Gadang Priyotomo; Sakhiah Abdul Kudus (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Corrosion represents a major concern in numerous industrial sectors, primarily due to the inherent vulnerability of metallic structures to degradation. Therefore, implementing effective corrosion protection measures is essential. Naturally occurring organic chemical compounds and important molecules have demonstrated strong potential for corrosion protection. Some studies indicate that those containing oxygen, sulfur, and nitrogen in the atmosphere exhibit the highest protection performance. Organic and naturally derived protection generally functions by forming protective films on metal surfaces, thereby mitigating the corrosion rate. This review emphasizes the role of galvanized coatings as effective corrosion protection with the cathodic protection method and anode sacrificial on the steel surfaces. It also includes an analysis of steel surface morphology using SEM-EDS micrographs. The review was conducted following PRISMA guidelines, with literature sources covering publications. A total of selected studies were critically analyzed to examine corrosion types, protection mechanisms, efficiency performance, and surface characterization of galvanized coatings. Both Hot-Dip Galvanizing (HDG) and Cold Galvanizing Coatings (CGC) were systematically compared in terms of corrosion rate, protective efficiency, coating thickness, and environmental aggressiveness. The paper systematically covers different types of corrosion, available protection control methods, and corrosion mitigation techniques. It further explores protective mechanisms, evaluates efficiency, and identifies the most effective control strategies. Additionally, the review discusses theoretical approaches, activation parameters, adsorption studies, and surface morphology. This review highlights key factors influencing galvanized steel performance, including coating composition, environmental parameters, and exposure duration, while also identifying current research gaps. The findings provide valuable insights for optimizing corrosion protection strategies and improving the service life of steel structures in atmospheric environments.